Biomimetic Scaffold with Aligned Microporosity Designed for Dentin Regeneration - Panseri, Silvia; Montesi, Monica; Dozio, Samuele Maria; Savini, Elisa; Tampieri, Anna; Sandri, Monica (Frontiers in Bioengineering and Biotechnology, 2016)
Tooth loss is a common result of a variety of oral diseases due to physiological causes, trauma, genetic disorders and aging, and can lead to physical and mental suffering that markedly lower the individual’s quality of life. Tooth is a complex organ that is composed of mineralized tissues and soft connective tissues. Dentin is the most voluminous tissue of the tooth and its formation (dentinogenesis) is a highly regulated process displaying several similarities with osteogenesis. In this study gelatin, thermally denatured collagen, was used as a promising low-cost material to develop scaffolds for hard tissue engineering. We synthetized dentin-like scaffolds using gelatin biomineralized with magnesium-doped hydroxyapatite and blending it with alginate. With a controlled freeze-drying process and alginate cross-linking it is possible to obtain scaffolds with microscopic aligned channels suitable for tissue engineering. 3D cell culture with mesenchymal stem cells showed the promising properties of the new scaffolds for tooth regeneration. In detail, the chemical-physical features of the scaffolds, mimicking those of natural tissue, facilitate the cell adhesion, the porosity is suitable for long term cell colonization and fine cell/material interactions.